2013
DOI: 10.1111/1440-1630.12057
|View full text |Cite
|
Sign up to set email alerts
|

Positioning occupational therapy as a discipline on the research continuum: Results of a cross‐sectional survey of research experience

Abstract: A cohesive strategy should focus on consolidating Occupational Therapists' evidence-based practice skills and building confidence. Clinicians wishing to engage in research need access to academic support. Academics and clinicians should work closely to produce clinically relevant research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 30 publications
8
65
0
Order By: Relevance
“…One aim of the northern Queensland research capacity initiative is to increase HPs using and producing research. Using and producing research requires a continuum of skills with evidence‐based practice skills at one end and conducting research skills at the other . Our results demonstrate rural HPs possess skills to use research but need support to conduct research.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…One aim of the northern Queensland research capacity initiative is to increase HPs using and producing research. Using and producing research requires a continuum of skills with evidence‐based practice skills at one end and conducting research skills at the other . Our results demonstrate rural HPs possess skills to use research but need support to conduct research.…”
Section: Discussionmentioning
confidence: 83%
“…Our results demonstrate rural HPs possess skills to use research but need support to conduct research. HPs face many barriers conducting research, including lack of skills and training, and in rural areas, time and ability to backfill positions are particularly problematic …”
Section: Discussionmentioning
confidence: 99%
“…There have been repeated calls in the field of occupational therapy to increase research capacity, research outputs and strengthen the evidence base of the profession (Case-Smith & Powell, 2008;Pighills, Plummer, Harvey & Pain, 2013). Universities have an important role to play in the production and dissemination of research findings; charging academics with a moral and fiduciary responsibility to undertake research and to publish.…”
Section: Introductionmentioning
confidence: 99%
“…Hitch (2016) surveyed 41 mental health occupational therapists who generally held positive attitudes to EBP, and found that those with more post graduate training were more likely to try new or manualised interventions. Pighills et al (2013) conducted a survey of 86 Australian occupational therapists from a range of practice areas and concluded a high proportion are interested in research but had little experience and high support needs. Again, these studies give validity to the similar results found by Upton et al (2014).…”
Section: Literature Reviewmentioning
confidence: 99%